The Development of Interactive Audio-Visual-Based Media Using VideoScribe to Reduce Misconceptions Electrical Potential and ECG Material - Sihombing, Rizky Agassy; Muslim, Muslim; Rahman, Taufik (Tarbiyah : Jurnal Ilmiah Kependidikan, 2023)
This research aimed to assess the suitability of the developed Audio-Visual Media and its effectiveness in reducing student misconceptions. The research follows the R&D (Research and Development) approach, specifically utilizing the ADDIE development model developed by Branch. The research participants comprised 17 9th-grade students from SMP Swasta Hang Tuah 2 Medan. The research procedures included a pre-survey, instrument creation, survey and observation, and validation. The results of the developed media showed that the first indicator, related to the response to material presentation, fell within the "good" category, with a percentage of 80.20%. The second indicator, which assessed the attractiveness of Sparkol VideoScribe's video display, was categorized as "very good," with the highest percentage recorded at 84.25%. Similarly, the response to convenience, representing the third indicator, was considered "good" with a percentage of 80.81%. The fourth indicator was also classified as "good," with a percentage of 79.40%. Based on the data analysis, the developed media is deemed feasible and can be utilized effectively in science learning.